Characteristic, relationship and impact of thermokarst lakes and retrogressive thaw slumps over the Qinghai-Tibetan plateau - Wenwen Li; Denghua Yan; Yu Lou; Baisha Weng; Lin Zhu; Yuequn Lai; Yunzhe Wang (Geoderma)
Thermokarst lakes (TLs) and retrogressive thaw slumps (RTSs) are common thermokarst landscapes that play a crucial role in regulating hydrology, ecology, and biogeochemical elements in permafrost regions. However, how TLs, as water accumulation units, affect regional water imbalances remains unclear, and whether the slow movement of shallow soil material from RTSs disrupts ecosystem barriers is still unknown. Additionally, it is uncertain whether the expansion of TLs is influenced by RTS-induced disruptions to surface water flow paths. In this study, we integrated previous research, field surveys, and remote sensing imagery to determine the evolution patterns, spatial extent, and interactions between 39,766 TLs and 1,680 RTSs on the Qinghai-Tibetan Plateau (QTP). We further employed the eXtreme gradient boosting algorithm and ICESat-2 ATL08 laser altimetry data to quantify changes in water storage due to TLs. The results revealed that TLs and RTS followed different evolutionary trajectories from 2000 to 2020. Overlapping impact areas were observed only in the headwaters of the Changjiang River, where 22 TLs and 21 RTSs co-occurred, indicating that TL formation is mainlyunaffected by RTSs. Additionally, 98% of RTS patches showed increasing NDVI trends after losing their mattic layer, demonstrating that RTSs do not impose irreversible suppression on vegetation growth. This study also comprehensively quantified how TLs contribute to regional water imbalances across regional, sub-basin, and patch scales. Summarizing and identifying the links between TLs and RTSs at a large scale can provide valuable insights into the feedback mechanisms between ecological hydrological processes and climate warming in permafrost regions, offering a reference for similar studies.